The Persistence of Poverty in Peru: Possible Answers, their Limits and their lmplications for Latin America - Sheahan, John (2002)
In  the  1990s,  with  economic  liberalization at  the beginning of  the decade,  and with the end of  the extreme violence of  Sendero Luminoso from  1992, the  Peruvian eco- nomy went  through a period of recovery and rapid growth up to  1997. In that period * This  study  was  prepared for the  Boston lnstitute of  Development  Economics and Deve- lopment Alternatives,  Inc.,  with financing from the  U.S.  Agency for  lnternational  Develo- pment  for their project on  Pro-poor economic  growth  (contract PCE-1-03-0015-00). the incidence of  poverty came down from 55 to 51 percent. But growth stopped again at that point, and did not show any signs of revival until 2002. The main frustration for  Peruvians in the last decade has been the problem of finding employment that  is sufficiently productive to enable them to get out of  poverty. Even in the  period of  high growth from 1994 to  1997, employment conditions remained  so weak  that  real wages  of hourly paid production workers  fell. One  of  the greatest  di- sappointments of  the 1990s was  that  economic  liberalization,  and better results with economic growth,  did  not  do  more to  improve the balance between  the  overwhel- ming numbers of  low-skill workers  and the opportunities for  productive employment. A  major reason for  this failure  is that the structure of  comparative advantage,  led by the mining sector,  holds down the power of  growth to improve employment opportu- nities. That  structural handicap could  be  lessened by  using exchange  rate management to  raise incentives  for  exports and growth in manufacturing,  non-traditional agriculture, and modern services. It was  a costly mistake, from the viewpoint of  efforts to  reduce poverty, to allow an appreciation of  the real exchange rate at  the time of liberalization, and to  maintain that  unhelpful orientation until nearly the end of  the decade.  Many other factors have kept poverty at  high levels. One of  them is the  low supply of  arable land relative to the agricultural labor force. Another  is the low quality of public education. A third is that the  level of  taxation is too  low to provide sufficient fi- nancing for social investment.